Study Mechanical Properties of (Low Density of Polyethylene (LDPE) / Serpentine Mineral Powder) - muslim shaban, et.al, Raed (Al-Qadisiyah Journal of Pure Science, 2017)
Research include Effect of Mechanical properties of low density polyethylene (LDPE), which is manufactured in the General state company of petrochemical industries, Basra, as function of the percentages of serpentine mineral powder (0%,1%,2%, 3%, 4%,5% ), at particular size. (ï‚£ 250 ïm) were investigated through several variables, such as, strength, and elongation. The obtained results were appeared that the added minerals act to reduce the spaces between the polymer chains, which reflects the high ability of the polymer against the applied stress, and a high degree of homogeneity between the host polymer and the added fillers, the results lead to that the stress force behavior was better in percentage (1%) from composite, after decreasing the percentage with increase the filler. The composite effect serpentine mineral filler fill materials on Mechanical Properties of Low properties therefore stress force decrease in cutting, observed tensile decrease in all percentage.